Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

AI-driven non-intrusive occupant monitoring for occupant-centric control: A multi-domain review of thermal, air, and visual environments - Ji Young Yun; Jin Woo Moon; Kang Woo Bae; Jun Kyu Kim; Hae Won Lee; Hye In Kim; Jae Ho Sung; Michael Kim (Building and Environment, 2026)

Environment-responsive phase transformation of Ni-modified cobalt phosphate aerogels for durable hydrogen evolution in freshwater and seawater - Younghun Kim; Sang-Hyun Kim; Jiseung Kim; Wonjun Lee; Hyun Jee Heo; In Hye Kwak; Vinayak G. Parale; Hyung-Ho Park (Desalination, 2026)

Regenerative effects of myogenic gene transfected MSC derived exosomes on radiation esophagitis - Min-kyung Kim; In Gul Kim; So Young Eom; Yewon Kim; Jin-A. Kim; Jungirl Seok; Seok Chung; Hye-Joung Kim; Eun-Jae Chung (Tissue Engineering and Regenerative Medicine, 2026)
Background Radiation esophagitis is a common adverse effect of radiotherapy for head and neck cancers, and is marked by irreversible damage and fibrosis of esophageal muscle tissue. Although mesenchymal stem cell (MSC) therapy is emerging as a promising approach for tissue regeneration, clinical translation remains challenging due to issues with cell viability and differentiation in vivo. This study evaluates the regenerative efficacy of exosomes derived from MSCs transfected with myogenic genes (MyoD, Myogenin, Myf6, referred to as Myo-MIX) using a murine model of radiation-induced esophageal fibrosis. Methods Human adipose-derived MSCs were transfected with Myo-MIX plasmids by electroporation, and exosomes were collected from conditioned media using ExoQuick. Nanoparticle tracking analysis and transmission electron microscopy were employed to characterize exosomal size and morphology. A mouse model of localized radiation-induced esophageal injury (10 Gy × 2 fractions) was generated and followed by intramuscular administration of Myo-MIX exosomes. Regenerative and anti-fibrotic outcomes were examined through Masson’s trichrome staining, immunohistochemistry (α-SMA, Calponin, CD68), and quantitative RT-PCR. Results Treatment with Myo-MIX exosomes resulted in a pronounced decrease in fibrosis and inflammatory response compared to PBS-treated controls and naïve MSC-exosome groups. Enhanced restoration of muscular architecture was observed, accompanied by elevated expression of Calponin and α-SMA, and a reduction in CD68 + macrophage infiltration. Gene expression profiling indicated increased levels of myogenic and anti-fibrotic markers in the Myo-MIX exosome-treated group. Conclusion Exosomes from myogenic gene-transfected MSCs significantly enhance esophageal muscle regeneration and attenuate fibrosis after radiation-induced damage. This cell-free therapeutic approach holds potential as a novel and practical strategy for addressing radiation esophagitis in patients receiving radiotherapy for head and neck malignancies.

Unravelling the Population Genetic Dynamics of the Ivory Snail (Babylonia areolata) in Vietnam: Guiding Sustainable Aquaculture Development - Sang Van Vu; Angkasa Putra; Sarifah Aini; Imon Abedin; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Thanh Tat Le; Hoang Huy Nguyen; Hien Van Doan; In Van Vu; Hyun-Woo Kim; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Marine algae growth and carbon capture augmentation by antioxidant nanozymes - Supreetha Sivaraj; Hye-In Kim; Su-Ji Jeon; Arnav Deshpande; Conor P. Murphy; Sandeep Sharma; Robert E. Jinkerson; Lieve M.L. Laurens; Juan Pablo Giraldo (Algal Research, 2026)

Interaction between ethanol and flunitrazepam in rats: Pharmacokinetic mechanisms and toxicological implications - Yejin Kim; Jeong In Seo; Jin Ah Won; Sooyeun Lee; Hye Hyun Yoo (Chemico-Biological Interactions, 2026)

Pollution characteristics of PM2.5 and PM1.0 at urban and background sites in South Korea: Focusing on health risks of PAHs and heavy metals - Sang-Jin Lee; Ho-Young Lee; In-Gyu Cho; Seong-Joon Kim; Ji Yi Lee; Hye-Jung Shin; Young Sung Ghim; Yong Pyo Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Intestinal Accumulation of Polyester Microfibers Modulates HPG Axis Regulation and Oocyte Maturation in Zebrafish (Danio rerio) - Seungjun Kim; Jin Namgung; Hye-na Moon; In-kyu Yeo (Fishes, 2026)
Polyester microfibers (MF) are widespread in aquatic environments and increasingly recognized as an emerging factor affecting fish physiology. This study aimed to investigate the effects of intestinal accumulation of MF on gut tissue and cellular alterations, as well as on the HPG axis and oocyte maturation in adult female zebrafish. Adult female zebrafish were exposed to environmentally relevant concentrations of MF (1000 and 3000 particles/L) for 14 days to examine endocrine-regulated physiological and reproductive responses. For comparative reference, a bisphenol A (BPA) exposure group was included to contextualize endocrine-related responses. MF exposure resulted in intestinal accumulation. Gene expression analyses showed increased expression of vtg1 and esr2a, along with decreased expression of gnrh3, fshβ, lhβ, cyp17, and cyp19a1, indicating altered regulation of the HPG axis and steroidogenic pathways. Ovarian histology revealed alterations in oocyte development, especially at the higher MF concentration, indicating that MF can affect endocrine-regulated physiology and reproduction in fish. Together, these findings provide new evidence that intestinal accumulation of microfibers, along with associated histological and transcriptional alterations, elicits estrogen-responsive physiological patterns that influence HPG axis regulation and oocyte maturation in fish.

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

Effect of low-temperature storage regimes on the UV-B sensitivity of apple anthocyanin - Shucheng Duan; Ji Hye Kim; Min-Jea Kim; Chan Saem Gil; In-Kyu Kang; Seok Hyun Eom (Postharvest Biology and Technology, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

Assessment of mechanisms and efficiencies for Mn decrease at unit processes in passive treatment facilities for mine drainage - Hye-Lim Kwon; Duk-Min Kim; Seong-Sook Park; Ji-Hye Hong; Ju-In Ko (Environmental Geochemistry and Health, 2025)

A novel mechanistic model for diagnosing the general health status of kimchi cabbage using the discrete-pixel data - Sang-Deok Lee; You Jin Lim; Kyung-Hwan Yeo; Oak-Jin Lee; Yun-Soo Choi; Gyu Hyeon Park; Hyejin Lee; Hyo In Yoon; Taeyang Kim; Ji-Hye Moon (Computers and Electronics in Agriculture, 2025)

Collagenase and tyrosinase inhibitory compounds from fish gut bacteria Ruegeria atlantica and Pseudoalteromonas neustonica - Jonghwan Kim; Su Jung Hwang; Gyu Sung Lee; Ju Ryeong Lee; Hye In An; Hong Sik Im; Minji Kim; Sang-Seob Lee; Hyo-Jong Lee; Chung Sub Kim (Phytochemistry Letters, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Physicochemical characterization and in vivo assessment of novel apixaban-loaded polymeric nano-aggregates - Fakhar ud Din; Hye In Lee; Jung Suk Kim; Mi Ran Woo; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Estimation of BPA, BPS, and BPF exposure levels in the general Korean population using the physiologically-based toxicokinetic model and human urinary biomonitoring for risk assessment - Min-Ju Kim; Yong-Kook Kwon; Hyung-Jun Kim; Dong-Gyun Han; In-Soo Yoon; Seungyoung Park; Gunyoung Lee; Hye Young Lee (International Journal of Hygiene and Environmental Health, 2025)

Development of a novel apixaban-loaded solid self-emulsifying drug delivery system for oral administration: physicochemical characterization and pharmacokinetics in rats - Hye In Lee; Mi Ran Woo; Fakhar ud Din; Jung Suk Kim; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Salinity alternation with dark treatment enhances the gel quality and quantity of carrageenan in a red alga, Chondrus crispus - Hye-In Song; Ji-Sook Park; Jang K. Kim (Aquaculture, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Direct aluminate precipitation technique with a phase transformation strategy for selective lithium extraction from Uyuni brine - Hee Seo Kim; Yong Jae Suh; Dae-Woo Kim; Heeji Yoo; Hye-Jin Hong; In-Su Park (Chemical Engineering Journal, 2025)

NXP032 Improves Memory Impairment Through Suppression of Tauopathy in PS19 Mice and Attenuates Okadaic Acid-Induced Tauopathy in SH-SY5Y Cells - Hyeyoon Eo; Seong Hye Kim; In Gyoung Ju; Joo Hee Lee; Myung Sook Oh; Youn-Jung Kim (Journal of Neuroimmune Pharmacology, 2025)

How far have we come in our efforts to apply personalized therapy for lung cancer at bedside? - Hyun Soo Kim; In Kyoung Kim; Seul Bee Lee; Seo-Hee You; Chang Dong Yeo; Jin-A. Kim; Seok Chung; Sang Haak Lee; Hye Joung Kim (Molecular & Cellular Toxicology, 2025)

Establishment of circular economy by utilising textile industry waste as an adsorbent for textile dye removal - Jee Young Kim; Hye-Bin Kim; Dohee Kwon; Yiu Fai Tsang; In-Hyun Nam; Eilhann E. Kwon (Environmental Research, 2024)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

A new quantitative method to validate the expression of homoeologous genes in polyploids - Keunhwa Kim; Eun Song Lee; Smita Mirsyad Warsadiharja; Junwoo Lee; Hye-yeong Kang; Ji In Jang; Yu Seon Chae; Soon Ju Park (Plant Biotechnology Reports, 2024)

A hybrid tracking method for maritime obstacles using sensor data - Ha-Yun Kim; Myung-Il Roh; Hye-Won Lee; In-Chang Yeo; Yeong-Min Jo; Jisang Ha; Nam-Sun Son (Ocean Engineering, 2024)

Synergistic effects of multi-dimensionality in an aerogel for lithium-ion battery anodes with an enhanced capacitive contribution - Younghun Kim; Young Hwan Kim; Vinayak G. Parale; Sang-Hyun Kim; In Hye Kwak; Hyung-Ho Park (Chemical Engineering Journal, 2024)

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Nano-Sized rGO-Encapsulated TiO2 Nanowire-Filled PDMS cone type dielectric elastomer actuator operating at low applied electric field - Jin Sung Seo; Kyoung Tae Park; Su Min Oh; Hye In Kang; KiJong Kim; Sung-Hyeon Baeck; Sang Eun Shim; Yingjie Qian (Chemical Engineering Journal, 2024)

Correction to: Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)

Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)
With the increasing use of flattening filter free (FFF) beams, it is important to evaluate the impact on the skin dose and target coverage of breast cancer treatments. This study aimed to compare skin doses of treatments using FFF and flattening filter (FF) beams for breast cancer. The study established treatment plans for left breast of an anthropomorphic phantom using Halcyon’s 6-MV FFF beam and TrueBeam’s 6-MV FF beam. Volumetric modulated arc therapy (VMAT) with varying numbers of arcs and intensity modulated radiation therapy (IMRT) were employed, and skin doses were measured at five points using Gafchromic EBT3 film. Each measurement was repeated three times, and averaged to reduce uncertainty. All plans were compared in terms of plan quality to ensure homogeneous target coverage. The study found that when using VMAT with two, four, and six arcs, in-field doses were 19%, 15%, and 6% higher, respectively, when using Halcyon compared to TrueBeam. Additionally, when using two arcs for VMAT, in-field doses were 10% and 15% higher compared to four and six arcs when using Halcyon. Finally, in-field dose from Halcyon using IMRT was about 1% higher than when using TrueBeam. Our research confirmed that when treating breast cancer with FFF beams, skin dose is higher than with traditional FF beams. Moreover, number of arcs used in VMAT treatment with FFF beams affects skin dose to the patient. To maintain a skin dose similar to that of FF beams when using Halcyon, it may be worth considering increasing the number of arcs.

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Combination approach of paired starter culture and lactic acid on inhibiting autochthonous lactic acid bacteria for extending kimchi shelf life - Chang Hee Jeong; Hye In Ko; Mo Eun Lee; Sung-Gi Min; Mi-Ai Lee; Tae-Woon Kim (Food Control, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

S100A8/A9-RAGE pathway and chronic airway inflammation in smoke-induced lung carcinogenesis - Sung Bae Cho; In Kyoung Kim; Hye Seon Kang; Sang Haak Lee; Chang Dong Yeo (Molecular & Cellular Toxicology, 2024)

Linderae Radix Ameliorates Cognitive Dysfunction by Inhibiting Neuroinflammation and Synaptic Damage in Alzheimer’s Disease Models - Seong Hye Kim; In Gyoung Ju; Jin Hee Kim; Hyeyoon Eo; So-Ri Son; Dae Sik Jang; Myung Sook Oh (Molecular Neurobiology, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Effect of pulsed electric field pretreatment on mass transfer during hot air drying: Drying and rehydration properties of sweet potato - Si-Yoen Kim; Ui-Chan Jeong; Hye-In Ju; Seho Jeong; Dong-Un Lee (Innovative Food Science & Emerging Technologies, 2023)

Led-mediated instantaneous pore formation in membranes driven by structural transformation and deprotonation of phospholipids - Hui Bang Cho; Hye Jin Kim; Hye-Ryoung Kim; Sujeong Lee; Ji-In Park; Keun-Hong Park (Chemical Engineering Journal, 2023)

Adsorptive recovery of rare earth elements from aqueous solution by citric acid crosslinked carboxymethylated cellulose nanofibril aerogel - Hee Seo Kim; Dae-Woo Kim; In-Su Park; Hye-Jin Hong (Journal of Cleaner Production, 2023)

Magnetic flocculants and selective adsorbents for the decontamination of radioactive and acidic soil-washing effluent - Hye-Nim Kim; June-Hyun Kim; Ilgook Kim; In-Ho Yoon (Journal of Water Process Engineering, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Enhanced removal of cesium from hydrobiotite using polyacrylonitrile (PAN)-based nickel ferrocyanide beads - Hye-Nim Kim; June-Hyun Kim; Kyung Jin Lee; Ilgook Kim; In-Ho Yoon (Journal of Hazardous Materials, 2023)

Modeling for the estimating the adsorption property of fruit waste-based biosorbents for the removal of organic micropollutants - Bo-Gyeon Cho; Jae-Ho Lee; Hye-In Kim; Se-Been Mun; Se-Ra Jin; Dae Geun Kim; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Research, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Normobaric hyperoxia re-sensitizes paclitaxel-resistant lung cancer cells - Jeonghyeon Im; Hee Young Kwon; In Kyoung Kim; Chang Dong Yeo; Sei Won Kim; Heayon Lee; Hye Seon Kang; Sang Haak Lee (Molecular & Cellular Toxicology, 2022)

Double-blind randomized placebo-controlled study of the efficacy and safety of hair loss prevention shampoo containing salicylic acid, panthenol, and niacinamide in alopecia patients - Hee-Taek Kim; Hye-Su Park; Yong-Min Kim; In-Chul Lee; Sang-Jun Lee; Jae-Suk Choi (Toxicology and Environmental Health Sciences, 2022)

PKC-β modulates Ca2+ mobilization through Stim1 phosphorylation - Hye-Jin Song; In-Sook Jeon; Seung Ryul Kim; Kwan Sik Park; Jae-Won Soh; Kwang Youl Lee; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2022)
Background Calcium ions play a pivotal role in cell proliferation, differentiation, and migration. Under basal conditions, the calcium level is tightly regulated; however, cellular activation by growth factors increase the ion level through calcium pumps in the plasma membrane and endoplasmic reticulum for calcium signaling. Orai1 is a major calcium channel in the cell membrane of non-excitable cells, and its activity depends on the stromal interaction molecule 1 (Stim1). Several groups reported that the store-operated calcium entry (SOCE) can be modulated through phosphorylation of Stim1 by protein kinases such as extracellular signal-regulated kinase (ERK), protein kinase A (PKA), and p21-activated kinase (PAK). PKC is a protein kinase that is activated by calcium and diacylglycerol (DAG), but it remains unclear what role activated PKC plays in controlling the intracellular calcium pool. Objectives Here, we investigated whether PKC-β controls intracellular calcium dynamics through Stim1. Methods Several biochemical methods such as immune-precipitation, site directed mutagenesis, in vitro kinase assay were employed to investigate PKC interaction with and phosphorylation of Stim1. Intracellular calcium mobilization, via Stim1 mediated SOCE channel, were studied using in the presence of PKC activator or inhibitor under a confocal microscope. Results Our data demonstrate that PKC interacts with and phosphorylates Stim1 in vitro. phosphorylation of Stim1 at its C-terminal end appears to be important in the regulation of SOCE activity in HEK293 and HeLa cells. Additionally, transient intracellular calcium mobilization assays demonstrate that the SOCE activity was inhibited by PKC activators or activated by PKC inhibitors. Conclusion In sum, our data suggest a repressive role of PKC in regulating calcium entry through SOCE.

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Natural hybridization between transgenic and wild soybean genotypes - Do Young Kim; Jin Ho Heo; In Soon Pack; Jung-Ho Park; Min Shik Um; Hye Jin Kim; Kee Woong Park; Kyong-Hee Nam; Sung Duk Oh; Jae Kwang Kim; Ju Seok Seo; Chang-Gi Kim (Plant Biotechnology Reports, 2021)

Genetic analysis and population genetic structure of hard-shelled mussel, Mytilus coruscus Gould 1861 (Mytiloida: Mytilidae) from the coasts of South Korea based on mitochondrial cytochrome oxidase (COI) gene sequences - Chang Ho Yi; Moongeun Yoon; Ji Min Kim; Il-Hun Kim; In-Young Cho; Hye Suck An (Genes & Genomics, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

Spatio-temporal patterns of the minimum rest time for outdoor workers exposed to summer heat stress in South Korea - Seung-Wook Lee; In-Gyum Kim; Hye-Min Kim; Dae-Geun Lee; Hee-Choon Lee; Gwangyong Choi (International Journal of Biometeorology, 2020)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

De novo assembly and characterization of transcriptome in the medicinal plant Euphorbia jolkini - Neha Samir Roy; In-hye Lee; Jung-A Kim; Rahul Vasudeo Ramekar; Kyong-Cheul Park; Nam-il Park; Joo-Hong Yeo; Ik-Young Choi; Soonok Kim (Genes & Genomics, 2020)

Emergence of vancomycin-resistant Enterococcus faecium ST1421 lacking the pstS gene in Korea - Hye Mee Kim; Doo Ryeon Chung; Sun Young Cho; Kyungmin Huh; Cheol-In Kang; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Enhanced anti-ageing and wound healing properties of Ficus religiosa L. bark, leaf and aerial root extract in human keratinocytes cell line (HaCaT) - Prem Pandey; Hyo Hyun Seo; Hye-In Kim; Seung Hwan Ryu; Medini Dingre; Sang Hyun Moh; Atul Kulkarni; Varsha A. Parasharami (Vegetos, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Retained or altered expression of major histocompatibility complex class I in patient-derived xenograft models in breast cancer - In Hye Song; Young-Ae Kim; Hyeonjin Lee; Hye Seon Park; In Ah Park; Chan Kyu Sim; Myeong Sup Lee; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2019)

Length of poly(A) tail affects transcript infectivity of three ZYMV symptom variants differing at only five amino acid positions - Boram Kim; In-Sook Cho; Ik-Hyun Kim; Go-Woon Choi; Hye-Kyoung Ju; Wen-Xing Hu; June-Pyo Oh; Jung-Kyu Kim; Eunyong Seo; Leslie L. Domier; John Hammond; Hyoun-Sub Lim (Journal of Plant Pathology, 2019)

Amino acid differences in the N-terminal half of the polyprotein of Chinese turnip mosaic virus isolates affect symptom expression in Nicotiana benthamiana and radish - Wen-Xing Hu; Eun-Young Seo; In-Sook Cho; Jung-Kyu Kim; Hye-Kyoung Ju; Ik-Hyun Kim; Go-Woon Choi; Boram Kim; Chun-Hee Ahn; Leslie L. Domier; Sang-Keun Oh; John Hammond; et al. (Archives of Virology, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Spatial and temporal variations of volatile organic compounds using passive air samplers in the multi-industrial city of Ulsan, Korea - Seong-Joon Kim; Hye-Ok Kwon; Myoung-In Lee; Yongwon Seo; Sung-Deuk Choi (Environmental Science and Pollution Research, 2019)

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Inoculum effect of methicillin-susceptible Staphylococcus aureus against broad-spectrum beta-lactam antibiotics - Kyoung-Ho Song; Sook-In Jung; Shinwon Lee; Sohee Park; Eu Suk Kim; Kyung-Hwa Park; Wan Beom Park; Pyoeng Gyun Choe; Young Keun Kim; Yee Gyung Kwak; Yeon-Sook Kim; Hee-Chang Jang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Association of Periodontitis with the Concentration Levels of Germanium and Tin in Hair - Hye-Sung Kim; Hyun-Jae Cho; Soo-Myoung Bae; Young-Youn Kim; Sung-In Baek; Kwang-Hak Bae (Biological Trace Element Research, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Chemotactic effect of S100A8 and S100A9 on human eosinophilic leukemia cells, EoL-1 through TLR4 - Ayoung Gu; Da Hye Kim; Na Rae Lee; In Sik Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2018)

Elevated CO2 concentration affected pine and oak litter chemistry and the respiration and microbial biomass of soils amended with these litters - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Hye-In Yang; Kwang-Seung Lee; Young-Han Lee; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2018)

Seismicity of the 2016 ML 5.8 Gyeongju earthquake and aftershocks in South Korea - Jimin Lee; Yonggyu Ryoo; Sun Cheon Park; Young Mo Ham; Jong Soo Park; Myeong Su Kim; Sang Mi Park; Hyen Geom Cho; Keun Su Lee; In Sun Kim; Hye Su Kim; Sunhee Bae (Geosciences Journal, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Combined Poly(Lactide-Co-Glycolide) Microspheres Containing Diphtheria Toxoid for a Single-shot Immunization - Hye Seung Woo; Sung Rae Kim; Mikyeong Yoon; Eun Seok Lee; In Ho Chang; Young Mi Whang; Do Ik Lee; Myung Joo Kang; Young Wook Choi (AAPS PharmSciTech, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Whitening and anti-wrinkle activities of ferulic acid isolated from Tetragonia tetragonioides in B16F10 melanoma and CCD-986sk fibroblast cells - Hye-Jin Park; Jun-Hyo Cho; Shin-Hyub Hong; Dong-Hee Kim; Hee-Young Jung; In-Kyu Kang; Young-Je Cho (Journal of Natural Medicines, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Dynamical–statistical seasonal prediction for western North Pacific typhoons based on APCC multi-models - Ok-Yeon Kim; Hye-Mi Kim; Myong-In Lee; Young-Mi Min (Climate Dynamics, 2017)

Effect of house dust mite on neutrophil apoptosis by cytokine secretion in lymphocytes - Na Rae Lee; Ji-Sook Lee; Seung Yeop Baek; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Soo Jin Lee; In Sik Kim (Molecular & Cellular Toxicology, 2016)

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

LED light for in vitro and ex vitro efficient growth of economically important highbush blueberry (Vaccinium corymbosum L.) - Cao Dinh Hung; Chang-Hee Hong; Seon-Ki Kim; Kyu-Han Lee; Jea-Young Park; Min-Woo Nam; Dae-Ho Choi; Hye-In Lee (Acta Physiologiae Plantarum, 2016)

Molecular analyses of H3N2 canine influenza viruses isolated from Korea during 2013–2014 - EunJung Lee; Eun-Ju Kim; Bo-Hye Kim; Jae-Young Song; In-Soo Cho; Yeun-Kyung Shin (Virus Genes, 2016)

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4 - Kang-In Lee; Han-Gyu Choi; Yeo-Jin Son; Jake Whang; Kwangwook Kim; Heat Sal Jeon; Hye-Soo Park; Yong Woo Back; Seunga Choi; Seong-Woo Kim; Chul Hee Choi; Hwa-Jung Kim (Apoptosis, 2016)

House dust mite allergen suppresses neutrophil apoptosis by cytokine release via PAR2 in normal and allergic lymphocytes - Na Rae Lee; Seung Yeop Baek; Ayoung Gu; Da Hye Kim; Seong Yeol Kim; Ji-Sook Lee; In Sik Kim (Immunologic Research, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Benzo(a)pyrene represses melanogenesis in B16F10 mouse melanoma cells - Da Hye Joo; Hwa Jun Cha; Karam Kim; Minhee Jung; Jung Min Ko; In Sook An; Sung Nae Lee; Hyun Hee Jang; Seunghee Bae; Nam Kyung Roh; Kyu Joong Ahn; Sungkwan An (Molecular & Cellular Toxicology, 2015)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

A novel strain of porcine epidemic diarrhea virus in Vietnamese pigs - Yong Kwan Kim; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Eun-Hye Park; Van Phan Le; Nguyen Ba Hien; Pham Ngoc Thach; Do Hai Quynh; Tran Quang Vui; Nguyen Trung Tien; Dong-Jun An (Archives of Virology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

MicroRNA expression profiling of p-phenylenediamine treatment in human keratinocyte cell line - Hwa Jun Cha; Ok-Kyu Lee; Soo Yeon Kim; Jung-Min Ko; Su Young Kim; Ji Hye Son; Hyun Joo Han; Shunhua Li; Soo Young Kim; Kyu Joong Ahn; In-Sook An; Sungkwan An; et al. (Molecular & Cellular Toxicology, 2015)

Use of rhamnolipid biosurfactant for membrane biofouling prevention and cleaning - Lan Hee Kim; Yongmoon Jung; Sung-Jo Kim; Chang-Min Kim; Hye-Weon Yu; Hee-Deung Park; In S. Kim (Biofouling, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Isolation and characterization of polymorphic microsatellite markers from the Korean common squid Todarodes pacificus (Ommastrephidae) - Hye Suck An; Eun Mi Kim; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Polyphenols and antioxidant capacity of a spontaneous reddish mutant in Satsuma mandarin, Shinheungri - Min Young Kim; In-Jung Kim; Soon Jae Im; Ji Hye Kim; Ji-Man Heo; Seung-Yeob Song; Jung Hyun Kim; Seo Hyun Moon; Seongbeom Cho (Natural Product Research, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Genetic differences between broodstock and offspring of seven-band grouper in a hatchery - Hye Suck An; Jae Kwon Cho; Kyong Min Kim; Maeng Hyun Son; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Characterization of 22 polymorphic microsatellite markers for seven-band grouper Epinephelus septemfasciatus developed using a 454 pyrosequencing approach - Hye Suck An; Jae Kwon Cho; Kyong Min Kim; Maeng Hyun Son; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Global gene expression responses to waterlogging in leaves of rape seedlings - Yong-Hwa Lee; Kwang-Soo Kim; Young-Seok Jang; Ji-Hye Hwang; Dong-Hee Lee; In-Hu Choi (Plant Cell Reports, 2014)

Development of freshwater sediment management standards for organic matters, nutrients, and metals in Korea - In Ae Huh; Yong Seok Kim; Soon Ju Yu; Stella Wong; Won Sik Shin; Hye Ok Park; Ho Jeong Kim; Hyun Woo Kim (Environmental Science and Pollution Research, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Comparative genetic diversity of wild and hatchery-produced Pacific oyster (Crassostrea gigas) populations in Korea using multiplex PCR assays with nine polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Woo Jin Kim; Hyun Jeong Lim; Eun Mi Kim; Soon Gyu Byun; Young Baek Hur; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

N-terminal region of rice polycomb group protein OsEZ1 is required for OsEZ1–OsFIE2 protein interaction - Jong-Kuk Na; Mi-Hye Seo; Seok-Jun Moon; In-Sun Yoon; Yeon-Hee Lee; Jae Kwang Kim; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Erratum to: Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2013)

Antisense-overexpression of the MsCOMT gene induces changes in lignin and total phenol contents in transgenic tobacco plants - Eun Soo Seong; Ji Hye Yoo; Jae Geun Lee; Hee Young Kim; In Seong Hwang; Kweon Heo; Jae Kwang Kim; Jung Dae Lim; Erik J. Sacks; Chang Yeon Yu (Molecular Biology Reports, 2013)

The green algae Ulva fasciata Delile extract induces apoptotic cell death in human colon cancer cells - Min Ju Ryu; Areum Daseul Kim; Kyoung Ah Kang; Ha Sook Chung; Hye Sun Kim; In Soo Suh; Weon Young Chang; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Selenium Significantly Inhibits Adipocyte Hypertrophy and Abdominal Fat Accumulation in OLETF Rats via Induction of Fatty Acid β-Oxidation - Ji Eun Kim; Sun Il Choi; Hye Ryun Lee; In Sik Hwang; Young Ju Lee; Beum Soo An; Sang Hak Lee; Hak Jin Kim; Byeong Cheol Kang; Dae Youn Hwang (Biological Trace Element Research, 2012)

Chronological changes in inflammatory cytokines immunoreactivities in the mouse hippocampus after systemic administration of high dosage of tetanus toxin - Bing Chun Yan; Joon Ha Park; In Hye Kim; Bich Na Shin; Ji Hyeon Ahn; Ki-Yeon Yoo; Deuk-Sik Lee; Myong Jo Kim; Il-Jun Kang; Moo-Ho Won (Experimental Brain Research, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Involvement of rice Polycomb protein OsFIE2 in plant growth and seed size - Jong-Kuk Na; Mi-Hye Seo; In-Sun Yoon; Yeon-Hee Lee; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

3′,4′-Dihydroxyflavonol reduces vascular contraction through Ca2+ desensitization in permeabilized rat mesenteric artery - Hye Young Kim; Young Mi Seok; Owen L. Woodman; Spencer J. Williams; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

An improved method of protein isolation and proteome analysis with Saccharina japonica (Laminariales) incubated under different pH conditions - Eun-Young Kim; Dong-Gyun Kim; Yu-Ri Kim; Hye-Jung Hwang; Taek-Jeong Nam; In-Soo Kong (Journal of Applied Phycology, 2011)

Cloning, expression, and PCR application of DNA polymerase from the hyperthermophilic archaeon, Thermococcus celer - Kee Pum Kim; Heejin Bae; In Hye Kim; Suk-Tae Kwon (Biotechnology Letters, 2011)

Effects of gomisin A on vascular contraction in rat aortic rings - Young Mi Seok; Young Whan Choi; Gyung-Duck Kim; Hye Young Kim; Yoh Takuwa; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

Ocean–atmosphere coupling and the boreal winter MJO - Hye-Mi Kim; Carlos D. Hoyos; Peter J. Webster; In-Sik Kang (Climate Dynamics, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Sll0396 regulates transcription of the phycocyanin genes in Synechocystis sp. PCC 6803 - In-Hye Oh; Ho-San Kim; Young-Ho Chung; Young-Hye Kim; Young Mok Park (Plant Biotechnology Reports, 2010)

Isolation of S-adenosyl-L-methionine synthetase gene from Panax ginseng C.A. meyer and analysis of its response to abiotic stresses - Rama Krishna Pulla; Yu-Jin Kim; Shohana Parvin; Ju-Sun Shim; Jung-Hye Lee; Yeon-Ju Kim; Jun-Gyo In; Kalai Selvi Senthil; Deok-Chun Yang (Physiology and Molecular Biology of Plants, 2009)

Enhanced fungal resistance in Arabidopsis expressing wild rice PR-3 (OgChitIVa) encoding chitinase class IV - Jung-Hun Pak; Eun-Sook Chung; Sang-Hyun Shin; Eun-Hee Jeon; Mi-Jin Kim; Hye-Young Lee; Ji-Ung Jeung; Nam-In Hyung; Jai-Heon Lee; Young-Soo Chung (Plant Biotechnology Reports, 2009)

The impact of ocean–atmosphere coupling on the predictability of boreal summer intraseasonal oscillation - Hye-Mi Kim; In-Sik Kang (Climate Dynamics, 2008)

Optimization of octanoic acid and sulfur donor concentrations for lipoic acid production by Pseudomonas reptilivora - Jung-Hwan Ji; In-Sik Yu; Hye-Jung Kim; Deok-Kun Oh (Biotechnology Letters, 2008)

Interannual variations of the boreal summer intraseasonal variability predicted by ten atmosphere–ocean coupled models - Hye-Mi Kim; In-Sik Kang; Bin Wang; June-Yi Lee (Climate Dynamics, 2008)

Isolation and structural analysis of bamylocin A, novel lipopeptide from Bacillus amyloliquefaciens LP03 having antagonistic and crude oil-emulsifying activity - Sang-Cheol Lee; Sun-Hee Kim; In-Hye Park; Soo-Yeol Chung; Yong-Lark Choi (Archives of Microbiology, 2007)

Gene Cloning, Sequencing, and Expression of an Esterase from Acinetobacter lwoffii I6C-1 - Hye Eun Kim; In Soo Lee; Joo Hwan Kim; Kyu Woong Hahn; Ul Jae Park; Hyon Soo Han; Kyeong Ryang Park (Current Microbiology, 2003)